Judicial Connectivity in the Case of Firearm Sales by Military Personnel to Civilians : a Review of Military and General Court Decisions in Indonesia - Hardiyanto, Benediktus Sulistyo; Wisnubroto, Aloysius; Widiartana, G. (LOCUS MEDIA PUBLISHING, 2025)
This article aims to find out and analyze the settlement of cases of connexity between military personnel and civilians in the sale and purchase of assembled firearms as well as the political views of the law regarding future cases of connexity. Laws, rules, and judicial rulings are the subjects of this normative legal study. Data sources are primary, secondary and tertiary legal materials. The results showed that the resolution of the military-civilian connexity case in Military Court Decision Number 70-K/Pm Iii-18/Ad/X/2021 & District Court Decision Number 99/Pid.Sus/2021/Pn Sml was not carried out in accordance with the Criminal Code, the Criminal Procedure Code, the Military Justice Law and the Judicial Power Law because it was carried out separately. The political view of the law regarding the resolution of koneksitas cases is that there have been several legal reforms regarding koneksitas cases in Indonesia, but they have not been implemented until now, therefore there must be firmness and commitment from law enforcers to implement them.